Outbreak of extended-spectrum beta-lactamase-producing Klebsiella pneumoniae in a neonatal intensive care unit: Risk factors and key preventive measures for eradication in record time - María Fernández-Prada; Carmen Martínez-Ortega; Guillermo Santos-Simarro; Patricia Morán-Álvarez; Ana Fernández-Verdugo; Marta Costa-Romero (Elsevier, 2019)
Introduction: In November 2014, an extended-spectrum beta-lactamase producing Klebsiella pneumoniae outbreak was detected in the neonatal intensive care unit of a tertiary care hospital. Objective: Our aim was to determine the clinical, epidemiological and microbiological characteristics of the outbreak, to analyse the identified risk factors and to describe the preventive and control measures implemented for its eradication. Methods: We conducted a case-control study. We performed univariate and bivariate analyses, defining statistical significance as a P-value of less than 0.05. The implemented preventive and control measures were aimed at establishing the magnitude of the outbreak, effective communication, the evaluation of health care processes and education on patient safety. Clinical samples were collected for molecular and phenotypic characterisation. Findings: The sample consisted of 51 newborns, of who 17 were cases and the remaining 34 controls. The distribution of cases by birth weight was: 2 cases (11.8%) greater than 2500 g, 4 cases (23.5%) between 1500 and 2500 g, 5 cases (29.4%) between 1000 and 1500 g, and 5 cases (29.4%) less than 1000 g. In one case, the birth weight was not documented in the health record. The following risk factors for colonisation or infection were statistically significant in our study: presence of a central venous catheter (OR, 5.0 [95% CI, 1.4-17.8]; P = .016); parenteral nutrition (OR, 6.8 [95% CI, 1.8-25.7]; P = .006); urinary catheterization (OR, 5.9 [95% CI, 1.2-30.0]; P = .028) and birth weight (P = .035). We found statistically significant differences in the mean total length of stay in hospital (P = .004) and length of stay in the NICU (P = .002). All 17 cases presented antimicrobial resistance with presence of extended-spectrum beta-lactamase type CTX-M-14. Conclusion: Workplace interventions focused on patient safety need to be reinforced, especially those concerning practices with the potential to increase the extrinsic risk of colonisation or infection by extended-spectrum beta-lactamase-producing K. pneumoniae in the NICU, such as the insertion, care and maintenance of central venous catheter, parenteral nutrition and urinary catheterization. Resumen: Introducción: En noviembre de 2014, se detectó un brote de Klebsiella pneumoniae productora de betalactamasas de espectro extendido en la unidad de cuidados intensivos neonatales de un hospital terciario. Objetivo: El objetivo fue describir las características clínicas, epidemiológicas y microbiológicas del brote, analizar los factores de riesgo asociados y presentar las medidas preventivas y de control implementadas para su erradicación. Métodos: Estudio de casos y controles. Se realizaron análisis univariantes y bivariantes, considerándose estadísticamente significativo un valour de p < 0,05. Las medidas preventivas y de control se centraron en la necesidad de determinar la magnitud del problema, en la comunicación efectiva, la evaluación de los procedimientos sanitarios y la educación sobre la seguridad del paciente. Se realizó caracterización molecular y fenotípica de muestras clínicas. Resultados: La muestra de estudio consistió en 51 neonatos, de los que 17 fueron casos y los 34 restantes controles. La distribución de casos por peso al nacer fue: 2 con peso > 2.500 g (11,8%), 4 con peso de 1.500-2.500 g (23,5%), 5 con peso de 1.000-1.500 g (29,4%) y 5 con peso < 1.000 g (29,4%). En un caso no se había registrado el peso al nacer en la historia clínica. Los factores de riesgo estadísticamente significativos para la colonización/infección fueron: presencia de catéter venoso (OR = 5,0 [IC 95% 1,4-17,8]; p = 0,016); nutrición parenteral (OR = 6,8 [IC 95%: 1,8-25,7]; p = 0,006); sondaje vesical (OR = 5,9 [IC 95% 1,2-30,0]; p = 0,028) y peso al nacer (p = 0,035). Encontramos diferencias estadísticamente significativas en la estancia hospitalaria media (p = 0,004) y los días de estancia en la unidad de cuidados intensivos neonatales (p = 0,002). Se encontró resistencia a antimicrobianos tipo betalactamasas de espectro extendido CTX-M-14 en los 17 casos. Conclusión: Han de reforzarse las iniciativas de trabajo sobre la seguridad de los pacientes, especialmente aquellas aplicables a intervenciones con el potencial de aumentar el riesgo de colonización/infección por K. pneumoniae productora de betalactamasas de espectro extendido en la unidad de cuidados intensivos neonatales, como las asociadas a la inserción, cuidado y mantenimiento de catéter venoso, la nutrición parenteral y el sondaje vesical.